Socio-Economic Factors Contributing to Female Students’ Dropout in Community Technical Colleges in Thyolo and Phalombe Districts: A Case of Milonga and Naminjiwa Technical Colleges - Moyo, Alfred; Sankhulani, Lilian; Namalima, Stella (Journal of Education and Practice, 2022)
Most students in community technical colleges dropout before completion of their training course, particularly female students, which is counterproductive with regard to women empowerment. This paper therefore, reports on a study that was conducted at Milonga and Naminjiwa community technical colleges in Thyolo and Phalombe districts respectively. Thus, the study sought to establish probable socio-economic factors that influence dropout of female students from the two colleges, with a view of finding solutions to the problem. The two colleges were earmarked for the study because of their proximity to tea estates where manpower is the main source of labour for the tea industry. In addition, people in the two districts have similar cultural beliefs and economic status. Population of the study covered both female and male students including principals and instructors of the two technical colleges. In addition, identified parents of female students who dropped out of school were also part of the study. Thus, the study was conducted through qualitative research method so as to have an in-depth understanding of people views. Data was collected with reference to objectives of the study and then thematically analyzed. The study revealed several socio-economic factors that contribute to dropout of female students from the two colleges such as: cost of training and poverty, domestic chores and parents' characteristics, cultural factors, early marriages and gender difference including training environment. However, the relationship among students and instructors showed that it had no effect on dropout as it was cordial and amicable. Recommendations to policy makers and other stakeholders were proposed as follows: Government and Ministry of Labour Skills and Innovation should have a national policy to provide bursaries and loans to needy students. The government should construct hostels at the two colleges to have conducive training environment. Ministry of Labour Skills and Innovation should organize awareness campaign programmes to sensitize the community surrounding the two colleges on the importance of TVET. Ministry of Labour Skills and Innovation should recruit more female instructors to act as role models to other female students.